Outcome of Pregnancy in Chromosomally Normal Foetus with Increased Nuchal Translucency - S, Ranjit; P, Carol; C, Kellie; M, Pauline; S, Renuka (IIUM Medical Journal Malaysia, 2018)
Objective: The aim of this study is to evaluate the outcome of pregnancy in prenatal and postnatal period of pregnancy complicated with thick nuchal translucency but normal karyotype. Methods: This is a retrospective study of 119 singleton pregnancies with increased NT (NT > 2.5mm) but a normal karyotype over a 3 year period. The records of ultrasound at 18-20 and 25-26 weeks’, antenatal and postnatal details were reviewed. The developmental and health outcomes of the surviving children were obtained through telephone conversation with the family. Adverse outcome such as miscarriages, termination of pregnancy, intrauterine death, structural anomalies and neurodevelopment delay were analysed. Results: Out of 119 foetuses with increased NT but normal karyotype, 11.8% of pregnancies ended with miscarriages, termination of pregnancy and intrauterine death. 89.9% foetuses were structurally normal. 12.9% presented with structural anomalies in the second-trimester ultrasound scan. 81.8% showed major malformations, out of which 44% consisted of heart defects. 1% of foetuses were syndromic and 1.9% had developmental delay. 96.8% of foetuses with NT equal to or greater than the 95th percentile (3.4mm) and 80% with NT equal to or greater than the 99 percentile (5.5mm) had a normal outcome. 50% of foetuses with thickened nuchal fold had a poor outcome. Postnatal follow-up was established for all infants and toddlers, and abnormalities were observed in 5.6% of them. Chances of having a live and healthy infant decreases with increased NT, corresponding to 80% for NT equal to or greater than 5.5mm. Conclusion: We have provided data that may help in the counselling of parents and increasing their confidence on a favourable pregnancy outcome. In cases with increased nuchal translucency but normal karyotype, the chances of normal pregnancy success rate is 89.9%. Parents can be reassured that thickened nuchal translucency with a normal karyotype and normal targeted ultrasound between 20-22 weeks gestation, the risk of adverse perinatal outcome and postnatal developmental delay is not increased in comparison with that of the general population. This seems to be the case for all degrees of increased nuchal translucency.